Butyrophilin 3A (BTN3A, CD277)‐specific antibody 20.1 differentially activates Vγ9Vδ2 TCR clonotypes and interferes with phosphoantigen activation. Issue 6 (27th April 2017) - Starick, Lisa; Riano, Felipe; Karunakaran, Mohindar M.; Kunzmann, Volker; Li, Jianqiang; Kreiss, Matthias; Amslinger, Sabine; Scotet, Emmanuel; Olive, Daniel; De Libero, Gennaro; Herrmann, Thomas
Abstract : Vγ9Vδ2 TCR transductants show a TCR‐CDR3 specific response to phosphospantigens (PAg) and the BTN3‐specific mAb 20.1. mAb 20.1 abolishes PAg reponse of transductants with CDR3 not responsive to mAb 20.1 and reduces PAg response of clonotypes with an intermediate response to mAb 20.1. Abstract : Phosphoantigens (PAgs)‐like HMBPP (( E )‐4‐hydroxy‐3‐methyl‐but‐2‐enyl diphosphate) and butyrophilin 3 (BTN3A, CD277)‐specific monoclonal antibody 20.1 induce TCR‐mediated activation of Vγ9Vδ2 T cells. Here, we compared murine reporter cells transduced with Vγ9Vδ2 TCRs G115, D1C55, and MOP for the activation in culture with human RAJI cells and PAgs or mAb 20.1 and its single‐chain (sc) derivative. All transductants responded readily to PAg but only TCR MOP γ‐chain‐expressing cells responded to mAb/sc 20.1. Furthermore, both antagonist and agonist mAb and sc of the agonist mAb inhibited the PAg response of TCR‐transduced murine reporter cells. These findings suggest that, in contrast to stimulation by physiological stimulators (PAg), the responsiveness to mAb 20.1 depends strongly on CDR3 sequences of the TCR, and that mAb 20.1 can interfere with the PAg‐response. Mouse or human origin of reporter cells might affect the mAb 20.1 response since all three TCR‐mediated mAb 20.1‐induced activation of TCR‐transduced Jurkat cells. The pronounced differences between PAg and mAb 20.1‐induced activation observed here help to understand the often contradictory published data. This study provides novel perspectives on the physiological mechanism of Vγ9Vδ2 T‐cell activation, and highlights the complex mode of action of BTN3A‐specific antibodies as agents in cancer immunotherapy.